PENGARUH VIRAL MARKETING, GAYA HIDUP DAN INFORMASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN SKINCARE SKINTIFIC DI KOTA BATAM - Eban, Hendrika Noviana Lengi; Nainggolan, Nora Pitri (SCIENTIA JOURNAL, 2025)
This research aims to examine the influence of viral marketing, lifestyle, and product information on purchasing decisions for Skintific skincare in Batam City. This study uses a quantitative research method. The research sample consisted of 100 respondents, all women aged 13-40 years who use Skintific products in the Bengkong District of Batam City. The data collection method used is primary data. Data processing uses the SPSS Version 26 program. Based on the data and analysis that have been done, this study shows that viral marketing positively and significantly influences purchasing decisions for Skintific skincare in Batam City. In addition, lifestyle positively and significantly influences purchasing decisions for Skintific skincare in Batam City. Product information positively and significantly influences purchasing decisions for Skintific skincare in Batam City. And simultaneously, viral marketing, lifestyle, and product information positively and significantly influence purchasing decisions for Skintific skincare in Batam City.